Genesis of Federalism in Pakistan: A Historical Analysis - Abdul Shakoor Chandio; Taha Shabbir; Muhammad Nadeemullah; Asim Ali (Har Press Indonesia, 2021)
This article would attempt explore the roots of federation of Pakistani with respect to analyzing its political and Constitutional history from the British India. Because the idea of federation in this region has its roots in that period. The ideas of federalism emerged from the British introduced constitutional schemes. In response to that schemes, Congress and Muslim League had its own demands and which manifest their particular orientation for federalism. The theme of this article is to explore the differences of Congress and Muslim League on the federal arrangement in British India and on the future union of India. In this regard position of Muslim League is especially put in to consideration that what the party has its ideology regarding the federal form of government. For understanding the nature of Muslim league’s ideology regarding federalism, the politics and policies of Muslim League are studied in this article. This article poses challenge to the claims which are taken as granted that the League was a champion in demanding the maximum provincial autonomy in British India. The article would also highlight role of Leagues’ politics in Muslim Majority provinces to understand its nature of politics for federal arrangement in India. The important question that why Pakistan did not been a viable federation is sought out in the nature of Muslim Leagues politics in British India. A content analysis method is adopted which is qualitative study to find the historical context of evolution of federalism in Pakistan.